An agent-based model of the foraging ascomycete hypothesis. (October 2020) - Thomas, Daniel C.; Vandegrift, Roo; Roy, Bitty A.
Abstract: Most trees host hundreds of species of fungi asymptomatically in their internal tissues, known collectively as fungal endophytes. The Foraging Ascomycete (FA) hypothesis proposed that some fungal endophytes inhabit the internal leaf tissue of forest trees in order to enhance dispersal to substrates on the forest floor, by using leaves as vectors and as refugia during periods of environmental stress. This dispersal strategy has recently been termed viaphytism and is now thought to apply to fungal groups beyond ascomycetes. Viaphytism implies that many fungi may be in continuous and cyclical flux between life stages as endophytes in the forest canopy and as wood-decomposing fungi on the forest floor. This cycle may represent a very common and previously-ignored process in the ecology of forests, with implications for forest health. The ecological consequences of the viaphyte lifestyle are complex, so we constructed an agent-based model to explore it. Our model is intended to serve as both an explicit conceptual explanation of viaphytism, and as an exploration of the conditions in which a strategy of endophytism accompanied by leaf dispersal may be advantageous for fungi. In a scenario of a viaphytic fungal species on a model forest landscape, without fungal competitors, viaphytism is predicted to be a plausible alternative to dispersal to substrates by spores alone, allowing the fungus to persist reliably in the landscape. In a scenario that allows competition from aggressively dispersed non-viaphytic fungi, the model predicts some competitive benefits to fungal dispersal via leaves. However, these benefits are conditional, requiring sufficient retention through time of endophyte infections by host trees, and sufficient host trees in the landscape. In the model, loss of these fungal populations can result from increased local disturbances of forest canopy, and deforestation.